JUAL BELI AIR SUMBER DALAM PERSPEKTIF ETIKA BISNIS ISLAM DI DESA CANDIWATES KECAMATAN PRIGEN KABUPATEN PASURUAN - Khoiriyah; Aslikhah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
Islam is a source of values ​​and ethics in all aspects of overall human life, including business discourse. One of the unique teachings of Islam is to teach its adherents to carry out economic practices based on Islamic norms and ethics. In this association of life every person has an interest in other people therefore rights and obligations arise. This interaction has many benefits, especially for the fulfillment of basic living needs such as eating, drinking and so forth. Especially in the case of drinking humans need water as a basic need. Water is a resource that is needed by all people in the world and becomes something that is very vital, even for the entire life of living things on this earth. As is the case of trading water in Candiwates Village, Prigen District, Pasuruan Regency. The method used in this research is a qualitative method using case studies. This research uses the method of collecting observation, interview and documentation data. The results of this study conclude that the application of Islamic business ethics in Candiwates Village, Prigen District, Pasuruan Regency is in accordance with the concept of Islamic business ethics which includes unity, justice, responsibility, free will and honesty. But they pay less attention to the implementation of social and environmental responsibility.